Interscholastic sports participation among selected private secondary schools students in osogbo, Nigeria (2014)
This study investigated interscholastic sports participation of selected private secondary school students in Osogbo, Osun State, Nigeria. The study used simple random sampling technique to select 20 private secondary schools and 500 respondents while a self developed, structured and validated questionnaire with reliability index of 0.95 was used for data collection. The data were analyzed with both descriptive statistics of percentages and inferential statistics of Chi-square at 0.05 alpha level. The result showed that inadequate personnel, improper programming and lack of motivation are some of the factors militating against private secondary school students' participation in interscholastic sports in Osogbo. The results were discussed, conclusions drawn and recommendations that will assist in the proper implementation of interscholastic sports objectives among private secondary school students were also offered